Qualitative Evaluation of a Comprehensive Online Wellness Program (MENTOR) Among People With Spinal Cord Injury - Rimmer, James H.; Wilroy, Jereme; Young, Hui-Ju; Young, Raven; Sinha, Tanvee; Currie, Madison; Lima, Carla Rigo; Lai, Byron (Frontiers in Rehabilitation Sciences, 2022)
People with spinal cord injury (SCI) experience a plethora of health conditions that hinder their health and wellness. This qualitative retrospective evaluation describes the perceptions of 14 people with SCI, several months after they completed an eight-week telewellness community program (MENTOR – Mindfulness, Exercise and Nutrition To Optimize Resilience). The program offered daily online classes that covered three core wellness domains (mindfulness, exercise, nutrition) and one health coaching session to introduce participants to eight other wellness domains (sleep, self-care, core values, arts & leisure, outdoor time in nature; spiritual practice, relationships, contribution to others). Qualitative analysis resulted in 4 themes related to program benefits, likes, and improvement recommendations. First, participants valued the program for the social support provided by a sense of community and relationship building with peers. Second, self-regulation was facilitated by the comprehensiveness of the program components, easy online access, and shared lifestyle goals for self-improvement among peers. Third, participants reported improved psychological wellbeing and adopted healthy behaviors that were maintained long after the program. Last, future programs should include flexible class times, post-program support, specific exercise adaptations for people with limited arm function, and supplementary in-person meetings. These preliminary findings demonstrate that MENTOR may benefit the wellbeing of people with SCI and warrant further study.